(3GdUMGaI GdfSGFjI aj GdhWf GdYQHj (B/s - (3EHQGgje,ESeGYjd s ((3GdbGgQI (B:s (3GdOGQ GdOhdjI ddfTQ h GdJhRjY ,s, 1996)
(3jYO gPG GdcJGH GdeQLY GdChd aj GddZI GdYQHjI GdPj jDQN dfTCI h JWhQ GdUMGaI GdfSGFjI aj GdhWf GdYQHjq (B,(3efP Cf CUOQJ gfO fhad Chd eLdI fSGFjI YQHjI h gj eLdI (B-(3GdaJGI(B- (3HdEScfOQjI aj (B20(3fhaeHQ (B1892(3e h MJi fgGjI YGe (B1994(3e h bO CMUi GdeDda (B-(3NdGd gPG GdcJGH (B-(3eG jRjO Ydi (B180(3eLdI GeQGI h CSQI YQHjI dGjRGd jUOQ efgG CcKQ ef (B40 (3eLdI (B,(3HjfeG de jMU (B-(3Odjd GdOhQjGJ h GdUMa GdLGQjI aj GdhWf GdYQHj (B, (3GdPj CUOQJg GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe (B-(3Hcd JhGaQ dgG ef EecGfjGJ (B-(3ZjQ (B20(3eLdI GeQCI YQHjI h aj Led bdjdI (B. s
Keywords: (3GdhWf GdYQHj s; (3GdUMGaIs